Pengaruh Fasilitas Kantor dan Pelayanan Pegawai terhadap Kepuasan Masyarakat Kelurahan Bajubang Kabupaten Batang Hari - Budi Darma; Kasiyati Yunita Wulansari; Ratumas Hartha Delima (Universitas Batanghari Jambi, 2023)
This study discusses the effect of office facilities and employee services on community satisfaction in Bajubang Village, Batang Hari Regency. This study aims to determine the effect of office facilities and employee services on community satisfaction in Bajubang Village, Batang Hari Regency. In this study using Multiple Linear Regression Analysis in the analysis because it uses more than one independent variable. This study also uses the t test, F test, and the coefficient of determination. In the t-test and F-test, office facilities and employee service variables have an influence separately (partially) as well as jointly (simultaneously) on the satisfaction of the people of the Bajubang Village. In testing the Coefficient of Determination, office facilities and employee services affect the satisfaction of the people of the Bajubang Village by 84.5%. While 15.5% which affects the satisfaction of the people of the Bajubang Village is influenced by other variables not examined in this study.